Perilaku Cinta Rupiah Peserta Didik di SDN 27 Ladang Hutan Kecamatan Baso - Adi Warman (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The Love the Rupiah Movement is a national initiative launched by Bank Indonesia to instill a sense of patriotism through education about the Rupiah currency. This movement has three main pillars: understanding the Rupiah, caring for the Rupiah, and using the Rupiah wisely. This study aims to describe and analyze the Rupiah-loving behavior of students at SD Negeri 27 Ladang Hutan, as well as to identify the extent of students' understanding and practices in valuing the national currency as a symbol of national sovereignty. This study employs a qualitative descriptive approach with data collection techniques including observation, interviews, questionnaires, and documentation. The research subjects were fourth and fifth grade students, classroom teachers, the school principal, and several parents. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that most students are familiar with the types of Rupiah currency (82%) and have a fairly good understanding of the characteristics of genuine currency (45%). However, concrete behavior in caring for money is still low (38%), as are saving habits (35%) and the ability to distinguish between needs and wants (30%). Factors influencing the low practice of love for the Rupiah include a lack of thematic education in the curriculum, a lack of examples from the surrounding environment, and the suboptimal involvement of parents. In conclusion, there is a gap between students' understanding and practice in applying the values of Rupiah love. Therefore, the integration of Rupiah love values into thematic learning, co-curricular activities such as market day, and closer collaboration between schools and parents is needed. This study recommends strengthening financial literacy from an early age as part of continuous character education.